Attitudes Toward the Legitimacy of Management Efforts to Influence Employees - Davis, Keith (Academy of Management Journal, 1968)
Responses of sixty regular Air Force personnel to the Schein-Ott legitimacy questionnaire are compared with earlier responses of labor leaders, university students, and company executives. Rank-order correlations among the groups are + .88 or higher. Items of high legitimate influence involve job performance, the work environment, and off-the-job conduct which affects organizational interests. Items of low legitimacy concern private acts not directly involving the job or organization.